Perbedaan Keefektifan Minuman Jeruk Nipis Dan Jahe Merah Terhadap Emesis Gravidarum - Fitriana, Ratih; Sukamto, Edi; Siregar, Nursyahid (Bunda Edu-Midwifery Journal (BEMJ), 2024)
The incidence of hyperemesis gravidarum in Indonesia in 2019 was 1,904 people (5.42 percent) out of 25,234 pregnant women who checked themselves into health care facilities. The guidelines issued by the American College of Obstetrics and Gynecology (ACOG) say that treating emesis gravidarum should begin with non-pharmacological therapy. The purpose of this study was to determine the differences in the effectiveness of lime and red ginger drinks against emesis gravidarum at PMB EKAWATY. Methods research Quasi-experimental research with the Two Group Pretest Posttest design. The design of this study was carried out in two different groups that received different treatments. The study population consisted of 26 people, for each group 13 lime respondents and 13 red ginger respondents. The sampling technique uses total sampling. Statistical test used Wilcoxon test and Mann Whitney test. Results The significance value of ρ 0.002 less than 0.05 or ρ less than α in drinking lime, as well as in red ginger drinks obtained a significance value of 0.001 less than 0.05 or ρ less than α. The difference test using the Mann-Whitney test obtained a significance value of ρ 0.377 more than 0.05 or ρ more than α. Lime and red ginger drinks can reduce emesis gravidarum, namely there are ingredients in each, namely Flavonoids in lime and essential oil in ginger. Lime and red ginger drinks can reduce emesis gravidarum. There was no difference between drinking lime or red ginger and emesis gravidarum at PMB Ekawaty with a ρ value of 0.377 more than 0.05